2009
DOI: 10.1007/s10231-009-0112-y
|View full text |Cite
|
Sign up to set email alerts
|

Periodic homogenization of nonlinear non-monotone parabolic operators with three time scales

Abstract: Multiscale homogenization of nonlinear non-monotone degenerated parabolic operators is investigated. Under a periodicity assumption on the coefficients of the operators under consideration, we obtain by means of multiscale convergence method, an accurate homogenization result. It is also shown that in spite of the presence of several time scales the global homogenized problem is not a reiterated one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…a i (x; t; x="; t="; v 0 (x; t); v(x; t)) on Q, as an element of L 1 (Q), denoted by a " i ( ; v 0 ; v). We have the following result whose proof is exactly the same as that of [45,Proposition 3.1] and is therefore omitted. …”
Section: Y;mentioning
confidence: 99%
“…a i (x; t; x="; t="; v 0 (x; t); v(x; t)) on Q, as an element of L 1 (Q), denoted by a " i ( ; v 0 ; v). We have the following result whose proof is exactly the same as that of [45,Proposition 3.1] and is therefore omitted. …”
Section: Y;mentioning
confidence: 99%
“…We prove by means of very weak multiscale convergence [2] that the corrector 2 associated with the gradient for the second rapid spatial scale 2 actually vanishes. Already, in [3,4], it was observed that having more than one rapid temporal scale in parabolic problems does not generate a reiterated problem and in this paper we can see that nor does the addition of a spatial scale if it is contained in a coefficient that is multiplied with the time derivative of .…”
Section: Introductionmentioning
confidence: 84%
“…Parabolic homogenization problems for ≡ 1 have been studied for different combinations of spatial and temporal scales in several papers by means of techniques of two-scale convergence type with approaches related to the one first introduced in [5], see, for example, [2,3,[6][7][8], and in, for example, [9][10][11], techniques not of two-scale convergence type are applied. Concerning cases where, as in (1) above, we do not have ≡ 1, Nandakumaran and Rajesh [12] studied a nonlinear parabolic problem with the same frequency of oscillation in time and space, respectively, in the elliptic part of the equation and an operator oscillating in space with the same frequency appearing in the temporal differentiation term.…”
Section: Introductionmentioning
confidence: 99%
“…It then generated a great number of research activities that increases over time as shown by the vast existing literature to date; see, e.g., [2,3,5,6,20,37,38,41] and the references therein. However, being strictly limited to periodic structures, it quickly showed its inadequacy as far as the non periodic phenomena are concerned, since in nature, few physical phenomena have in fact a periodic behaviour.…”
Section: Introductionmentioning
confidence: 99%